Singular spectrum analysis to estimate core inflation in Brazil - Matheus Fellipe de Oliveira Santos; Rafael Morais de Souza; Wilson Luiz Rotatori Corrêa (Central Bank Review, 2024)
This paper presents a set of new core inflation measures for Brazil based on the Singular Spectrum Analysis (SSA) method. The measures are based on the official target used in the Brazilian inflation targeting regime. The period of analysis ranges from the beginning of the inflation targeting regime in 1999 and 2021. The SSA measures were compared to the inflation core ones used by the Central Bank of Brazil, through the evaluation of unbiasedness, short-term adjustment dynamics and predictive ability. The measures estimated by SSA meet the desired properties and have a greater predictive capacity than the other inflation cores.